Evaluation of Urine Procalcitonin, Interleukin-6, Heparin Binding Protein, Leukocyturia, and Bacteriuria for Early Detecting Urinary Tract Infection - Hani Susianti; I Putu Adi Santosa; Antonius Johanes; Esther Mayrita; Thiba Dina Merdikaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2019)
Urinary Tract Infection (UTI) is a common infectious disease. Urine culture as a gold standard is less practical and time- consuming. Examination of urine dipstick and microscopic is less accurate. Procalcitonin (PCT), IL-6 and Heparin Binding Protein (HBP) have known increase after infection, which potentially used for early detection of UTI. The aim of this study was to determine the diagnostic performance of urine IL-6, HBP, PCT, leukocyturia and bacteriuria level as biomarkers of UTI. The study was conducted on 51 UTI patients with positive urine culture, 16 UTI patients with negative urine culture, and 16 healthy control. Urine IL-6, HBP, and PCT level were determined using ELISA. Leukocyturia and bacteriuria were measured using automated flowcytometry and fluorescent dye analyzers. The gold standard for UTI diagnosis was urine culture. The sensitivity and specificity of urine PCT, IL-6, HBP, leukocyturia and bacteriuria were 60.78% and 65.62%; 72.55% and 56.25%; 96.07% and 50.00%; 80.39% and 78.12%; 80.39% and 59.09% respectively. The AUC of urine PCT, IL-6, HBP, leukocyturia and bacteriuria were 0.600; 0.605; 0.666; 0.877 and 0.830 respectively. For combinations of two biomarkers, the best sensitivity and specificity was demonstrated by urine PCT and leukocyturia.